Synthesis of budgeting and accounting standard method for «responsibility centers» as information engineering base of operating activities of enterprise - I.A. Herasymovych (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
Market conditions have caused the necessity of introduction at Ukrainian enterprises such a new economic mechanism as financial engineering based on the new approach of synthesis budgeting, «responsibility centers» and managerial accounting by the statutory method in the option of «Direct-costing» (direct costs). The new register «Report of the responsibility center about the work of the pair» which is created in direct costs, is offered for controlling of indexes of the proven budgets about their actual implementation. The main results of the research are: the clear definition of «centers of responsibility» and liability of managers for each item of estimates (budget); the creation of the accounting data signal system about the deviations from standards and changing of the budget norms; the development of operational, accounting records for daily cost accounting; the development of the graphs of document flow on each «responsibility center», which will provide the drafting of internal reporting for implementation of informational indicators, which give an opportunity to evaluate and to control, to predict and to plan the «responsibility centers» activity of an enterprise and also of some of its managers. Scientific novelty and practical value lie in the capacity of «Direct-costing» in terms of financial engineering: 1) it provides rapid determination of budget implementation and the actual cost of production; 2) it allows to determine the «break-even point» which enables to regulate it by options for varying the direct costs or volume and price for selling; 3) according to this method there is no necessity to allocate managerial fixed costs for types of products, as we cannot include them into the results of an enterprise activity.